Modeling and risk analysis of brine mixing mobile unit operation processes. Issue 7 (3rd July 2017) - Perisic, Jasmina; Milovanovic, Marina; Petrovic, Ivana; Radovanovic, Ljiljana; Ristic, Marko; Perisic, Velimir; Vrbanac, Maja
ABSTRACT: This work presents an approach to modeling and risk analysis of operating processes of a brine mixing mobile unit. The main objective was to identify the operations for which the mobile unit was designed as well as to identify all the stakeholders, conditions, requirements, and interactions that occur in the process. Based on these data, a model of the entire process was made, using the BPMN 2.0. notation. This model presents in detail all relevant activities and conditions so that on the basis of it, initial algorithms in the process of execution were established, and then the configurations for the controllers and the user application were made. Furthermore, a detailed analysis of the process in terms of risk assessment and identifying potential failures was made. The primary goal of the research was to describe the use of modeling and the process analysis as well as to point out the critical points and possible improvements of describing the solution.